Protective effects of Centella asiatica on cognitive deficits induced by D-gal/AlCl3 via inhibition of oxidative stress and attenuation of acetylcholinesterase level - Chiroma, Samaila Musa; Baharuldin, Mohamad Taufik Hidayat; Mat Taib, Che Norma; Amom, Zulkhairi; Jagadeesan, Saravanan; Adenan, Mohd Ilham; Mahdi, Onesimus; Mohd Moklas, Mohamad Aris (MDPI, 2019)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder with cholinergic dysfunctions and impaired redox homeostasis. The plant Centella asiatica (CA) is renowned for its nutritional benefits and herbal formulas for promoting health, enhancing cognition, and its neuroprotective effects. The present study aims to investigate the protective role of CA on D-gal/AlCl3-induced cognitive deficits in rats. The rats were divided into six groups and administered with donepezil 1 mg/kg/day, CA (200, 400, and 800 mg/kg/day) and D-gal 60 mg/kg/day + AlCl3 200 mg/kg/day for 10 weeks. The ethology of the rats was evaluated by the Morris water maze test. The levels of acetylcholinesterase (AChE), phosphorylated tau (P-tau), malondialdehyde (MDA) and activities of superoxide dismutase (SOD), in the hippocampus and cerebral cortex were estimated by enzyme-linked immunosorbent assay (ELISA). Additionally, the ultrastructure of the prefrontal cortex of the rats’ was observed using transmission electron microscopy (TEM). Rats administered with D-gal/AlCl3 exhibited cognitive deficits, decreased activities of SOD, and marked increase in AChE and MDA levels. Further, prominent alterations in the ultrastructure of the prefrontal cortex were observed. Conversely, co-administration of CA with D-gal/AlCl3 improved cognitive impairment, decreased AChE levels, attenuated the oxidative stress in hippocampus and cerebral cortex, and prevented ultrastructural alteration of neurons in the prefrontal cortex. Irrespective of the dose of CA administered, the protective effects were comparable to donepezil. In conclusion, this study suggests that CA attenuated the cognitive deficits in rats by restoring cholinergic function, attenuating oxidative stress, and preventing the morphological aberrations.